Drum rhythm therapy: An intervention to stimulate the cognitive abilities of children with Autism Spectrum Disorder (ASD) - Fauziah, Nailul; Prasetyo, Anggun Resdasari; Kustanti, Erin Ratna; Crescenzo, Pietro; Suryanto, Suryanto (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2022)
Children with Autism Spectrum Disorder (ASD) face obstacles in their cognitive development. This study aims to determine the effectiveness of the drum rhythm therapy model in stimulating cognitive abilities (attention, concentration, and short-term memory) in children with ASD. The experiment method was used with a one-group pretest-posttest design. Attention and concentration levels were measured both before and after therapy through a series of observations. A total of 14 children with ASD aged 4–12 participated in the study. All the participants were new students at Gilang Ramadhan Studio Band (GRSB), Surakarta, Indonesia. The drum rhythm therapy was employed with the participants for three months. Data analysis was conducted using Wilcoxon test analysis in SPSS Version 23. Results: The 14 participants showed an increase in attention, concentration and short-term memory scores following the therapy (Z = -2.533b, p = .011, p < .05). The results of the study could support the use of the alternative therapy with ASD children to increase their attention, concentration and short-term memory.